Recombination dynamics and EPR spectra of the primary radical pair in bacterila photosynthetic reaction centers with blocked electron transfer to the primary acceptor - Till, U; Klenina, I; Proskuryakov, I; Hoff, A; Hore, P (1997)
Recent electron paramagnetic resonance (EPR) experiments (Proskuryakov, I. I.; Klenina, I. B.; Hore, P. J.; Bosch, M. K.; Gast, P.; Hoff, A. J. Chem. Phys. Lett. 1996, 257, 333) on the primary radical pair in bacterial reaction centers are interpreted in detail. The spin-correlated radical pair model is extended to include the time dependence of the EPR intensities, differential lifetime broadening of the basic four-line spectrum, and averaging over the inhomogeneous distributions of hyperfine interactions in the two radicals. Values of the singlet and triplet recombination rate constants and the magnitude and sign of the exchange interaction of the radical pair are obtained from the shape and linewidth of the spin-polarized EPR spectra and the kinetics of formation of the triplet state of the primary electron donor. For Rhodobacter sphaeroides at 70 K, ks = (1.2 ± 0.3) × 107 s-1, kT = (5.7 - 8.8) × 108 s-1, -J = 8 - 6 G; and for Rhodopseudomonas viridis at 190 K, ks = (8 ± 2) × 107 s-1, kT = (6.5 - 10.0) × 108 s-1, -J = 17 - 16 G. The reliability of these values is discussed in the light of the energetic heterogeneity of the radical pair energies (Ogrodnik, A.; Keupp, W.; Volk, M.; Aumeier, G.; Michel-Beyerle, M. E. J. Phys. Chem. 1994, 98, 3432-3439) and of the sensitivity and selectivity of the EPR measurements toward the three parameters.